Optimization of Web-Based Integrated Management System Audit Process with System Development Life Cycle (SDLC) Appro - Haikal, Riyan; Arhami, Arhami; Iskandar, Iskandar (International Journal Labs, 2025)
PT Pupuk Iskandar Muda as a strategic industrial company has implemented the Pupuk Iskandar Muda Management System (SMPIM) which integrates various ISO and non-ISO standards. In the implementation of SMPIM's internal audit, there are operational constraints, especially in the management of follow-up audit findings that are still carried out manually and separately, causing time inefficiencies and prone to errors. This research aims to optimize the audit process of an integrated management system through the development of a website-based system using the System Development Life Cycle (SDLC) approach. The research method used a quasi-experiment pre and posttest without control group involving 41 internal auditors. Data analysis used descriptive statistics, Mann-Whitney U test, gap analysis, and Analytical Hierarchy Process (AHP). The results showed that the website system managed to significantly reduce the audit completion time from an average of 55.90 days to 26.35 days (p-value < 0.001). The AHP evaluation showed that the website method obtained a priority value of 0.873 compared to the manual method of 0.604. Gap analysis showed a variation in implementation achievement between management systems, with a significant increase in SMAP ISO 37001:2016 from 93% to 97%, while other systems experienced a decrease or stabilization. The development of a website system has proven to be effective in optimizing the internal audit process by providing easy access, real-time monitoring, and improving overall operational efficiency.